Sabores y Saberes. Capítulo 4 – Arroz de pescao - Cañas Carvajal, Paul David; Capacho Tirado, Diego Fernando (Universidad Autónoma de Bucaramanga UNAB, 2021)
Plato típico de Barrancabermeja, el arroz de pescado.